EFFECT OF TRIDAXPROCUMBENS EXTRACTS ON BLOOD CLOTTING - Pascal, Atchade S.; Ismael, Hoteyi; Soumanou, Seibou Toleba; Kaokab, Bello; Alphonse, Sezan (International Journal of Current Pharmaceutical Research, 2019)
Objective: The present work has focused on evaluating the effect of tridaxprocumbens on blood clotting. Methods: in the course of our study we have therefore carried out a Hydro ethanol extraction (50/50), Liquid-Solid extraction, and phytochemical screening. Thereafter our study was carried out on nine (09) male and female Wistar type rats aged from 10 to 12 w and weighing between 100 and 200 g. These animals were raised at the laboratory of Biomembranes Laboratory and Cell Signaling from FAST to UAC under standard environmental conditions. Animals have free access to water and food. 09 rats are experienced, divided in three batches of 3 rats each, submitted respectively to the following treatment: fed with distilled water, fed with 100 mg/kg P. C tridax extract procumbens, fed at 300 mg/kg P. C tridax extract procumbens. Evolution of the weight of rats during treatment was measured. After 7 d of treatment, the blood of the rats is taken for an experience of bleeding time, experience of coagulation time, and dosage of some blood parameters (platelet, partial thromboplastin, prothrombin). Results: Phytochemical screening carried out on the leaf and stem powder of Tridaxprocumbens revealed the presence of phenolic compounds, flavonoids, reducing sugar, mucilage, terpene and sterol, but at varying proportions. After 7 d of treatment, evaluation of the effect of the extractions on the body weight of the rats gave interesting conclusions. The weight of the control rats did indeed increase while that of the rats treated with the dose of (100 and 300 mg/kg) dropped. In addition, the effect of the hydroethanolic extract of the leaves and stems of Tridaxprocumbens on the coagulation of blood has been studied in order to verify the alleged property that the said extract can be used to manage bleeding. This was done by examining the effect of the extract on bleeding time, coagulation time, platelet count, activated partial thromboplastin time and prothrombin rate. These were carried out using the Duke method and the Lee and White method. In the bleeding time experiment, the mean time without adding the extract was 2.58±0.31 min, while the mean bleeding time after treatment with the extract was 1.61±0.70 min at a dose of 100 mg/kg PC and 1.77±0.69 min at a dose of 300 mg/kg PC, achieving 57% of the decrease in normal bleeding time. Thus the extract significantly lowers the bleeding time. When the extract was used for the coagulation time, it was found that the extract promotes blood clotting. In addition, this study reveals that Tridaxprocumbens significantly influences TCA, TP and platelet count at varying doses. Conclusion: The plant material studied in this study is, therefore, a credible alternative for an effective fight against bleeding and also promotes the coagulation of blood.